Acylsilanes in Iridium‐Catalyzed Directed Amidation Reactions and Formation of Heterocycles via Siloxycarbenes. (5th November 2015) - Becker, Peter; Pirwerdjan, Ramona; Bolm, Carsten
Abstract: Exposing ortho‐amido aroylsilanes to visible light or heat leads to cyclization reactions that provide N‐heterocyclic compounds via siloxycarbenes as key intermediates. The previously unreported starting materials have been prepared by directed amidations of aromatic acylsilanes in the presence of an iridium catalyst followed by N‐alkylation.